Rencana Zonasi Kawasan Konservasi Perairan Daerah Kota Pariaman, Provinsi Sumatera Barat - Suparno Suparno (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Pariaman City Marine Protected Area is a protected and managed water area including coastal waters of Angso Islands, Tangah Island, Ujuang Island, and Kasiak Island. The purpose of the study is to analyze the Zoning Plan of the Pariaman City Marine Protected Area and analyze the permitted and prohibited activities. The research method used a descriptive method. The results of the analysis of Zoning Plans for Marine Protected Areas covering an area of 11.776,63 Ha divided into 3 zones, namely no-take zone 249.31 Ha (2,12 %), sustainable fishery zones 11.460.32 ha (97,31%), and utilization zones 67,0 Ha (0,57%). Permitted activities in the no-take zone are research, ecosystem rehabilitation, and natural restocking. Sustainable fisheries zone are allowed for tourism, research, fishing, ecosystem rehabilitation, aquaculture, and natural restocking. A utilization zone is allowed for tourism, research, ecosystem rehabilitation, and natural restocking. Tourism, fishing, aquaculture, and activities that eliminate the area functionality are prohibited in the no-take zone area. The Activity that removes the function of the area is also prohibited in the fishery zone area. Activities that are forbidden in the utilization zone are for fishing, aquaculture, and activities that eliminate the function of the area. The Marine Protected Area Zoning Plan is an important document for the West Sumatra Provincial Government as the basis for granting marine business permits.